الخدمات التربوية المقدمة للطلبة ذوى صعوبات التعلم في المنطقة الشرقية في المملكة العربية السعودية: دراسة تقويمية من وجهة نظر العاملين وأولياء الأمور - ملحم، طارق بن يوسف مصطفى; القرني، عبدالله حسن (جامعه دمشق - كليه التربية, 2023)
هدفت الدراسة الحالية إلى تقويم الخدمات التربوية المقدمة للطلبة ذوي صعوبات التعلم من وجهة نظر العاملين وأولياء الأمور في المنطقة الشرقية. اتبعت الدراسة المنهج الوصفي التحليلي، وتكونت عينة الدراسة من (٢٤٠) مشاركا منهم (۱۰۰) مشارك من العاملين في برامج صعوبات التعلم بالمنطقة الشرقية اختيروا بطريقة عشوائية، و(١٤٠) من أولياء أمور الطلبة ذوي صعوبات التعلم. كما تم استخدام مقياس مستوى الخدمات التربوية المقدمة للطلبة ذوي صعوبات التعلم من إعداد الباحثين لجمع بيانات الدراسة أظهرت النتائج أن الخدمات التربوية المقدمة للطلبة ذوي صعوبات التعلم من وجهة نظر العاملين وأولياء الأمور في المنطقة الشرقية كانت بدرجة مرتفعة على مستوى جميع الخدمات التربوية، كما أشارت نتائج الدراسة إلى عدم وجود فروق ذات دلالة إحصائية في متوسطات تقديرات العاملين لمستوى خدمات الكشف والتشخيص والتقويم، وكذلك الخطط التربوية الفردية، والتجهيزات والوسائل التعليمية المستخدمة في تعليم الطلبة ذوي صعوبات التعلم باختلاف متغير الجنس، والمؤهل الأكاديمي، وسنوات الخبرة، كما أظهرت النتائج وجود فروق ذات دلالة إحصائية في مستوى البرامج العلاجية المقدمة للطلبة ذوي صعوبات التعلم لصالح معلمي صعوبات التعلم. وأوصت الدراسة بضرورة تطوير سياسات موحدة ذات علاقة بتقويم البرامج التربوية والخدمات المقدمة للطلبة ذوي صعوبات التعلم من خلال استلهام النماذج العالمية المتقدمة في الميدان. The current study aimed to assess the educational services provided for students with learning difficulties from the perspective of the teaching staff and parents in the Eastern Region. The current study used the descriptive analytical method. The total of participants was 240: 100 teaching staff who provided educational services to students with learning difficulties. They were selected randomly, and 140 parents of the students with learning difficulties who enrolled in the learning difficulties program in the Eastern region. To achieve the purposes of the study, the researchers developed a questionnaire for collecting data from the study and used the appropriate statistical tools. The results showed that evaluation of the educational services provided to students with learning difficulties from the perspective of the teaching staff and parents in the eastern region was at a high level in terms of all educational services. There were no statistically significant differences in means of estimations of the teaching staff about dimensions of the questionnaire due to the gender, academic qualification, and years of experience variables. The results also revealed that there were statistically significant differences in the dimension of the treatment programs provided for students with learning difficulties in favor of male teachers. The study recommended to develop unified policies related to evaluating educational programs and services provided to students with learning difficulties by drawing inspiration from advanced global models in the field.
Keywords: العملية التعليمية -- الأساليب تدريسية -- الأنشطة التربوية -- الخدمات الإرشادية